2015
DOI: 10.1016/j.jenvrad.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Depth distribution of cesium-137 in paddy fields across the Fukushima pollution plume in 2013

Abstract: Large quantities of radiocesium were deposited across a 3000 km(2) area northwest of the Fukushima Dai-ichi nuclear power plant after the March 2011 accident. Although many studies have investigated the fate of (137)Cs in soil in the months following the accident, the depth distribution of this radioactive contaminant in rice paddy fields requires further examination after the typhoons that occurred in this region. Such investigations will help minimize potential human exposure in rice paddy fields. Radionucli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…A similar situation was found in soil layers of paddy fields where the lands were tilled by farmers after the deposition of radionuclides (Lepage et al . ). In some sampling locations (PO‐12 bottom, PC‐12 middle, and PO‐13 middle and bottom), the concentration of radioactive Cs in the 10–20 cm layer was higher than that in the upper layers, indicating that plowing caused the migration of topsoil layers into the deeper layers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A similar situation was found in soil layers of paddy fields where the lands were tilled by farmers after the deposition of radionuclides (Lepage et al . ). In some sampling locations (PO‐12 bottom, PC‐12 middle, and PO‐13 middle and bottom), the concentration of radioactive Cs in the 10–20 cm layer was higher than that in the upper layers, indicating that plowing caused the migration of topsoil layers into the deeper layers.…”
Section: Discussionmentioning
confidence: 97%
“…; Lepage et al . ) after the 2011 NPP accident. Plowing can effectively decontaminate or reduce the radioactive pollution of crops harvested from those farmlands by moving the polluted surface layers to deeper locations (James and Menzel ; IAEA ).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic activities increase the depth of migration of radiocesium in the soil profile (Lepage et al, 2015;Matsunaga et al, 2013). Erosion and subsequent deposition processes may also result in the increase of radiocesium with depth in the soil profile similarly to carbon and other minerals in depositional landscapes (Van Oost et al, 2012).…”
Section: Figmentioning
confidence: 99%
“…Erosion and subsequent deposition processes may also result in the increase of radiocesium with depth in the soil profile similarly to carbon and other minerals in depositional landscapes (Van Oost et al, 2012). Lepage et al (2015) demonstrated that 90% of radiocesium remained in the upper 5 cm of the soil profile after deposition in non-cultivated soils, whereas within cultivated soils the contamination was homogeneous throughout the tilled soil layer (generally down to 15e30 cm). Endo et al (2013) demonstrated that radiocesium concentrations were not dependent on depth in rice paddy field soils, whereas they declined exponentially in an uncultivated soil.…”
Section: Figmentioning
confidence: 99%
“…According to the Japan Science Ministry, about 8% of the total national territory has been contaminated with 134 Cs and 137 Cs levels higher than 10 kBq m À2 for a total volume of contaminated soils of about 29 million cubic metres (Kobayashi et al, 2013). Estimations of 137 Cs total activity in the Fukushima Prefecture soils ranges between 10 and 50 PBq, with the highest values concentrated within a 70 km long radioactive plume where caesium soil contamination is in the range 100e600 kBq m À2 (Lepage et al, 2015). On the other hand, the average level for mandatory resettlement after the Chernobyl disaster was established at 148 kBq m À2 (Mallampati et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%